Policy networks reinforce climate-smart agriculture in Jamaica - Bafana, Busani; Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2019)
Amidst growing impacts of climate change, a threat to food security and livelihoods, Jamaica is using policy networks to scale-up climate-smart approaches helping farmers to be resilient and productive in extreme weather events.